Use of bupivacaine‐infused absorbable gelatin haemostatic sponge following eye enucleation in a corn snake. Issue 1 (14th October 2022) - Gomez‐Martinez, Maria Isabel; Kumaratunga, Vim; Khenissi, Latifa
Abstract: A 9‐year‐old, male, 0.69 kg, corn snake was referred for enucleation of its right eye. Pre‐anaesthetic medication consisted of butorphanol (1 mg/kg) and alfaxalone (10 mg/kg) intramuscularly. Orotracheal intubation was then performed. General anaesthesia was maintained with sevoflurane in 100% oxygen. During the general anaesthesia, the snake was manually ventilated. At the end of the surgery, the orbit was packed with a haemostatic sponge soaked in 0.75 mg/kg of 0.5% bupivacaine. Meloxicam (0.4 mg/kg) was administered subcutaneously as a part of the multimodal analgesic protocol. Total anaesthetic time was 90 minutes. Following 2 minutes of sevoflurane discontinuation, the snake started moving and the trachea was extubated. The snake displayed normal behaviour, although a short period of hypothermia was suspected in recovery. No other complications were encountered. The snake was discharged 4 hours after the end of surgery; meloxicam (0.2 mg/kg) was prescribed once daily, orally, for 14 days.